2015
DOI: 10.3171/2014.12.jns142059
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of skull base chondrosarcomas

Abstract: A lthough chondrosarcoma is the third most frequent primary malignancy of bone after myeloma and osteosarcoma, 7 skull base chondrosarcomas (SBCSs) are rare, accounting for only approximately 1% of all chondrosarcomas. 6 In France, intracranial chondrosarcomas account for 0.05% of all brain tumors, 21 and together with chordoma, they account for 0.09% of central nervous system tumors in the United States.5 However, among malignant bone tumors in the skull base, SBCS and chordoma are the 2 major histological ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…We observed several common chromosomal aberrations including loss of 1p, 10, and 13 and gain of 7 and 17q in our cohort (Figure 1a), consistent with the previous reports [8, 9]. Both chromosomal gain and loss of 7 and 10, respectively, are common genetic lesions, frequently observed in major malignant tumors including glioblastoma [10, 11], melenoma [12], and prostate cancer, [13] suggesting these alterations could be associated with tumor progression in chordoma as well.…”
Section: Resultssupporting
confidence: 92%
“…We observed several common chromosomal aberrations including loss of 1p, 10, and 13 and gain of 7 and 17q in our cohort (Figure 1a), consistent with the previous reports [8, 9]. Both chromosomal gain and loss of 7 and 10, respectively, are common genetic lesions, frequently observed in major malignant tumors including glioblastoma [10, 11], melenoma [12], and prostate cancer, [13] suggesting these alterations could be associated with tumor progression in chordoma as well.…”
Section: Resultssupporting
confidence: 92%
“…The effect of IDH mutations on patient outcome in this group is limited and most of the included studies did not provide survival data. Kanamori et al 23 reported an insignificant correlation of IDH1 mutation with tumor relapse but only seven patients were enrolled in their study. Additional studies are necessary to elucidate the prognostication of IDH1 / 2 mutations in chondrosarcomas of the head and neck.…”
Section: Discussionmentioning
confidence: 94%
“…Given the rarity of chondrosarcomas, 8 it was difficult to reach statistical significance when examining the prognosis of this tumor. Most of the published data failed to demonstrate the prognostic impact of IDH mutations in chondrosarcomas 17,23,26 . We incorporated nearly 500 cases of chondrosarcoma and highlighted that IDH mutation is an independent prognostic marker regardless of age, gender, tumor grades, and locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently detection of a variety of genetic differences have been used to characterise CS more thoroughly, e.g. detection of mutations by direct sequencing of isocitrate dehydrogenases 1 and 2 (IDH1/2) (19,20) . CS account for 10-20% of all malignant bone tumours most commonly arising in the long bones and pelvis (2,21,22) .…”
Section: Introductionmentioning
confidence: 99%